Why geology maps? - Stöcklin, J (Journal of Nepal Geological Society, 2008)
The geological map was and remains the fundamental document in classical geological exploration. In Nepal, geological information up to the middle of the 20th century was sporadic and geological maps were inexistent. With the opening of the country in 1950, a sharp rise of geological activity set in, and a wealth of factual information accumulated. Particularly in the 1970s, some excellent maps of selected parts of the High Himalaya were published by individual explorers, while maps of the geologically less spectacular but economically more important Lesser Himalaya were, even if not published, yet produced for public use by the Department of Mines and Geology, Government of Nepal. Observational facts had priority, interpretation and theory were of secondary importance. A change came about with the advent of plate tectonics. It brought important new insights into the interior of the Earth, turned the attention to the oceans, to crustal differentiations, to processes in the deeper layers of the Globe, and in general caused a shift of interest from the surface to the interior of our planet. With it went also a shift of balance from data to theory, from observation to speculation, from facts to fiction. “Models” largely replaced the maps. There remains, however, an unchanged responsibility of the geologist towards the community. He is expected to give answers to urgent geological problems facing people concerned with natural environment and hazards, with mineral resources and exploration, with hydropower, irrigation, soil conservation, with planning roads and dams, – in short, with problems related to the rocks that form the immediate ground on which we live. The geological map remains the fundamental document giving the answers to many of these questions, be it a map showing the general geology or a map focusing on a specific geological aspect. The choice of the principal subjects of this Congress (Regional Geology and Tectonics on the one hand, Natural Environment, Resources and Hazards on the other) and the maps and reports published in the last years by the Department of Mines and Geology and by the Geological Society of Nepal show that the responsible Institutions in this country follow a course that tries to keep a reasonable. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.1